FEATURES OF MANAGEMENT OF PATIENTS WITH CHRONIC HEART FAILURE AND DIABETES MELLITUS - Normatov Murod Buribayevich (Journals Park Publishing, 2022)
To study the effect of glycemic control on the development of diastolic dysfunction and remodeling of the left ventricle in patients with type 2 diabetes mellitus (DM) with the absence or presence of concomitant arterial hypertension.
Keywords: type 2 diabetes mellitus, diabetic cardiopathy, arterial hypertension.